Assessment of childhood undernutrition in India using National Family Health Surveys: Severity of anthropometric failure and contributing factors - Ramendra Nath Kundu; Md. Golam Hossain; Susmita Bharati; Ummay Ayesha; Shahara Sultana Shanta; Premananda Bharati (PLoS ONE, 2026)
Background Childhood undernutrition has a negative impact on healthy adulthood. Though progress is being made, a considerable number of children are still undernourished in India. The purpose of this study is to evaluate the prevalence of the severity of anthropometric failure (SAF) and its associated factors in India. Methods This study was carried out with a cross-sectional design at the household level. The data we utilized were secondary in nature and collected from all five phases of the National Family Health Surveys from 1992 to 2021. This study comprised 581124 under-five children in India. The severity of anthropometric failure (SAF) was assessed using the composite index of anthropometric failure (CIAF). Children can experience SAF in four ways, categorized as no anthropometric failure (AF), single AF, double AF, or triple AF. Results Over the past three decades, the prevalence of AF among under-five children in India has decreased. The latest NFHS survey indicates that the prevalence of AF was notably higher in rural areas (54.74%) compared to urban areas (47.73%). Single AF was a major issue in both rural (26.12%) and urban (25.37%) areas, while double AF presents a greater concern in rural areas (23.36%). Several socio-demographic and maternal factors have been identified as significant contributors to AF, particularly concerning low birth weight (LBW) and poor wealth index in both urban and rural contexts. In urban settings, AF was more prevalent among Muslim children and those whose mothers had lower levels of education. In rural areas, the condition was more common among children of underweight mothers and those from scheduled castes and scheduled tribes. Conclusions More than two-fifths of under-five children have either S-AF or D-AF, which was significant. The notably higher rates of undernutrition in rural areas highlight the urgent need for targeted interventions. Addressing these issues requires a comprehensive approach that focuses on improving maternal health, increasing educational opportunities, and implementing community-based nutrition programs, especially for vulnerable groups such as those from scheduled castes and tribes.